Molecular mechanisms and treatment strategies for Dupuytren’s disease - David B O’Gorman; Linda Vi; Bing Siang Gan (Dove Medical Press, 2010)
David B O’Gorman1,2,3,4, Linda Vi1,2,5, Bing Siang Gan1,2,3,5,61Cell and Molecular Biology Laboratory, 2The Hand and Upper Limb Centre, St. Joseph’s Health Care London, Schulich School of Medicine and Dentistry, 3Departments of Surgery, 4Biochemistry, 5Physiology and Pharmacology, 6Medical Biophysics, The University of Western Ontario, London, OT, CanadaAbstract: Dupuytren’s disease (DD) is a common disease of the hand and is characterized by thickening of the palmar fascia and formation of tight collagenous disease cords. At present, the disease is incurable and the molecular pathophysiology of DD is unknown. Surgery remains the most commonly used treatment for DD, but this requires extensive postoperative therapy and is associated with high rates of recurrence. Over the past decades, more indepth exploration of the molecular basis of DD has raised the hopes of developing new treatment modalities. This paper reviews the clinical presentation and molecular pathophysiology of this disease, as well as current and emerging treatment. It also explores the implications of new findings in the laboratory for future treatment.Keywords: Dupuytren’s contracture, Dupuytren’s disease, fibrosis